Hacking the Immune Response to Solid Tumors: Harnessing the Anti-Cancer Capacities of Oncolytic Bacteria - Jason M. Roe; Kevin Seely; Caleb J. Bussard; Emily Eischen Martin; Elizabeth G. Mouw; Kenneth W. Bayles; Michael A. Hollingsworth; Amanda E. Brooks; Kaitlin M. Dailey (MDPI AG, 2023)
Oncolytic bacteria are a classification of bacteria with a natural ability to specifically target solid tumors and, in the process, stimulate a potent immune response. Currently, these include species of Klebsiella, Listeria, Mycobacteria, Streptococcus/Serratia (Coley's Toxin), Proteus, Salmonella, and Clostridium. Advancements in techniques and methodology, including genetic engineering, create opportunities to "hijack" typical host-pathogen interactions and subsequently harness oncolytic capacities. Engineering, sometimes termed "domestication", of oncolytic bacterial species is especially beneficial when solid tumors are inaccessible or metastasize early in development. This review examines reported oncolytic bacteria-host immune interactions and details the known mechanisms of these interactions to the protein level. A synopsis of the presented membrane surface molecules that elicit particularly promising oncolytic capacities is paired with the stimulated localized and systemic immunogenic effects. In addition, oncolytic bacterial progression toward clinical translation through engineering efforts are discussed, with thorough attention given to strains that have accomplished Phase III clinical trial initiation. In addition to therapeutic mitigation after the tumor has formed, some bacterial species, referred to as "prophylactic", may even be able to prevent or "derail" tumor formation through anti-inflammatory capabilities. These promising species and their particularly favorable characteristics are summarized as well. A complete understanding of the bacteria-host interaction will likely be necessary to assess anti-cancer capacities and unlock the full cancer therapeutic potential of oncolytic bacteria.